An ex vivo Human Skin Model to Study Superficial Fungal Infections - Corzo-León, Dora E.; Munro, Carol A.; MacCallum, Donna M. (Frontiers in Microbiology, 2019)
Human skin fungal infections (SFIs) affect 25% of the world’s population. Most of these 21 infections are superficial. The main limitation of current animal models of human superficial 22 SFIs is that clinical presentation is different between the different species and animal models 23 do not accurately reflect the human skin environment. An ex-vivo human skin model was 24 therefore developed and standardised to accurately model SFIs. In this manuscript, we report 25 our protocol for setting up ex-vivo human skin infections and report results from a primary 26 superficial skin infection with Trichophyton rubrum, an anthropophilic fungus. The protocol 27 includes a detailed description of the methodology to prepare the skin explants, establish 28 infection, avoid contamination, and obtain high quality samples for further downstream 29 analyses. Scanning electronic microscopy (SEM), histology and fluorescent microscopy were 30 applied to evaluate skin cell viability and fungal morphology. Furthermore, we describe a 31 broad range of assays, such as RNA extraction and qRT-PCR for human gene expression, 32 and protein extraction from tissue and supernatants for proteomic analysis by liquid 33 chromatography-mass spectrometry (LC-MS/MS). Non-infected skin was viable after 14 34 days of incubation, expressed genes and contained proteins associated with proliferative, 35 immune and differentiation functions. The macroscopic damage caused by T. rubrum had a 36 similar appearance to the one expected in clinical settings, finally, using this model, the host 37 response to T. rubrum infection can be evaluated at different levels